Analisis Gerak Tari Buai-Buai Di Perguruan Seni Tradisi Singo Barantai Kelurahan Lubuk Lintah Kecamatan Kuranji Kota Padang - Shafana Aulia Azhara; Darmawati Darmawati (Institut Nalanda, 2023)
This research delves deeply into understanding the structure of the Buai-Buai Dance Movement, specifically within the context of Lubuk Lintah Village Traditional Art College in the Kuranji District of Padang City. This study falls under the category of qualitative research, employing descriptive methods. The primary research instrument is the researcher, supported by tools such as stationery, cameras, handy-cams, and flash devices. Data collection encompasses literature reviews, observations, interviews, and documentation. The data analysis process involves identifying, describing, clarifying, analyzing, and drawing conclusions from the data. The findings reveal that the comprehensive Buai-Buai Dance Movement in Lubuk Lintah can be examined through the lenses of space, time, and energy. In terms of spatial elements, it consists of 8 angular lines, 7 straight lines, and 1 curved line. The dominant volumes are large and medium volumes. The facing directions in the Buai-Buai Dance movement are 5 front, 3 back, 6 right side, 3 left side, 4 right diagonal, 5 left diagonal. In the mean time, the attention of view on the movement of the Buai Dance is more prevailing from here on out. The time part of the Buai Dance is overwhelmed by quick beat with a dreary (tedious) mood beginning to end (dull). Have a blissful impression in doing cultivating exercises. The energy part of the Buai Dance is areas of strength for overwhelmingly, predominant strain areas of strength for is a few developments have emphasizes. From the entire movement of the Buai Dance, it is investigated from the components of the dance development, in particular the spatial viewpoint, the time angle, the energy perspective which are interrelated from the impressions they create.